Parental influence on female vocational intentions in the Arabian Gulf. Issue 2 (2nd May 2017) - Rutledge, Emilie; Madi, Mohammed
Abstract : Purpose: The purpose of this paper is to examine parental career-related behavior (PCB) in relation to the vocational intentions of female nationals enrolled at higher education institutions in the United Arab Emirates. Design/methodology/approach: A conceptual framework was constructed to examine the interplay between the PCB factors of support, interference and lack of engagement, against context-relevant dimensions of gendered sociocultural barriers, public sector preferences and the likelihood itself of labor market entry. Survey data from face-to-face encounters ( n =335) was collected. Findings: Parental support was found to significantly reduce the perceived sociocultural barriers to workforce participation. Parental interference amplified these barriers and also increased public sector preferences. Those with educated fathers were more likely to seek labor market entry and consider atypical career paths, while those with a parent working in the private sector were more willing to consider this sector. Research limitations/implications: One limitation was a sample comprising only female students, nonetheless it implies PCB has an impact on "national" female labor force participation (FLFP). Therefore, seeking to engage parents as more active stakeholders in vocationally related HEI interventions would benefit from greater policy attention. Originality/value: This paper is the first to consider parental influence on FLFP using the PCB construct. Its value is in the framework model presented and its contribution to the discourse on the Arabian Gulf's labor market dynamics.